Tinjauan Kritis Kesyariahan Koperasi Syariah - Fidiana Fidiana (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
Cooperative sharia has a specific niche market, namely the micro businesses market in which consumen has emotional orientation. With these features, the cooperative sharia as a business entity have prosecuted profitable as well as fulfill the substance of sharia compliance. Profit orientation has been a common in the business world. How to sharia compliance? This study is aimed to examine sharia aspect of the cooperative by refering to sharia cooperative regulation provided. The study found some un-sharia implementation in term of substance, although the form or the packaging has looked as sharia. Un-sharia is looked from the scope of the savings and loans and financing, readiness to bear the loss, as well as the substance of the contracts.